Laajakaistaisen viranomaisviestintäpalvelun teknisen laadun mittaus - Pirinen, Riku (2025)
Authorities rely on mission-critical communication services to interact with their stakeholders during operational tasks. These services differ from consumer-grade communication solutions in that they must function reliably under all circumstances. Even brief degradations in service quality can have fatal consequences. As mobile network technologies evolve, the lifecycle of traditional narrowband public safety networks – now outdated and costly to maintain – is coming to an end. Around the world multiple projects are underway to gradually replace narrowband public safety communication services with broadband-based solutions that enable long-awaited, advanced features for end users. This transition is also taking place in Finland, where Virve, a TETRA-based network operated by the state-owned company Erillisverkot, has been in use for over 20 years. In the coming years, it will be replaced by the broadband-enabled Virve 2 service. The high reliability and performance of the existing TETRA implementation set a high bar for the new service. To optimize the technical performance of the new services, service providers must also update their quality measurement processes to meet the requirements of the broadband era. However, due to the novelty of this transition, no established methodology for quality measurement currently exists. The aim of this master’s thesis was to explore how the technical quality of broadband public safety communication services can be measured, with an emphasis on the end user experience. The objective was to design a solution tailored for Erillisverkot to measure the technical quality of broadband public safety communication service. The research followed design science methodology. The theoretical foundation was built through a literature review on public safety communication and both quality of service and quality of experience related literature in mobile network services. The empirical data was collected through a survey and field notes from workshop sessions. The developed solution was evaluated twice, and the improved version successfully met all predefined objectives. The final solution was presented within the target organization and accompanied by a preliminary deployment plan. As a result, this study provides a concrete quality measurement method for similar actors and introduces a theoretical framework suitable for quality measurement in the context of broadband-based public safety communication services.